2013
DOI: 10.1289/ehp.1206429
|View full text |Cite
|
Sign up to set email alerts
|

Health and Household Air Pollution from Solid Fuel Use: The Need for Improved Exposure Assessment

Abstract: Background: Nearly 3 billion people worldwide rely on solid fuel combustion to meet basic household energy needs. The resulting exposure to air pollution causes an estimated 4.5% of the global burden of disease. Large variability and a lack of resources for research and development have resulted in highly uncertain exposure estimates.Objective: We sought to identify research priorities for exposure assessment that will more accurately and precisely define exposure–response relationships of household air pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
202
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 241 publications
(212 citation statements)
references
References 67 publications
6
202
4
Order By: Relevance
“…While assessing exposure to HAP by type of cooking fuel used in the household is a crude estimate of exposure, having a high percentage of wood use within the solid fuel group eliminates some of the heterogeneity from categorizing all solid fuels together. 26 Our findings are consistent with other studies that found exposure to HAP is associated with an increased risk of under-five mortality. Bruce et al (2013) published a systematic review of outcomes associated with HAP for children 0-59 months.…”
Section: Discussionsupporting
confidence: 93%
“…While assessing exposure to HAP by type of cooking fuel used in the household is a crude estimate of exposure, having a high percentage of wood use within the solid fuel group eliminates some of the heterogeneity from categorizing all solid fuels together. 26 Our findings are consistent with other studies that found exposure to HAP is associated with an increased risk of under-five mortality. Bruce et al (2013) published a systematic review of outcomes associated with HAP for children 0-59 months.…”
Section: Discussionsupporting
confidence: 93%
“…The pollutants produced from combustion of solid fuels include suspended particulates (PM 10 and PM 2.5 ), carbon monoxide (CO), carbon dioxide (CO 2 ), nitrogen oxides (NO x ), sulfur dioxide (SO 2 ) and heavy metals (Clark et al, 2013). Combustion of biomass and coal is the dominant source of indoor air pollution in China Zhang and Smith, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These exposures are disproportionately experienced by women and children due to domestic roles typically encountered in least-developed or developing countries [2]. Average daily PM concentrations in homes burning solid fuels can range from 300 to 3,000 μg/m 3 [5,6], substantially greater than the World Health Organization guidelines for ambient and indoor air quality intended to protect public health (e.g., the guidelines for daily mean PM 2.5 [PM with an aerodynamic diameter less than or equal to 2.5 microns] and PM 10 are 25 μg/m 3 and 50 μg/ m 3 , respectively) [7]. Often characterized by large variability and uncertainty due to differences in factors such as stove use and time-activity patterns, household room configuration and ventilation, fuel type and moisture, weather, and instrument error [5], exposure to household air pollution has been linked to serious global health impacts, both acute and chronic [3].…”
Section: Introductionmentioning
confidence: 99%
“…Average daily PM concentrations in homes burning solid fuels can range from 300 to 3,000 μg/m 3 [5,6], substantially greater than the World Health Organization guidelines for ambient and indoor air quality intended to protect public health (e.g., the guidelines for daily mean PM 2.5 [PM with an aerodynamic diameter less than or equal to 2.5 microns] and PM 10 are 25 μg/m 3 and 50 μg/ m 3 , respectively) [7]. Often characterized by large variability and uncertainty due to differences in factors such as stove use and time-activity patterns, household room configuration and ventilation, fuel type and moisture, weather, and instrument error [5], exposure to household air pollution has been linked to serious global health impacts, both acute and chronic [3]. Air pollution from household solid fuel combustion is the third leading risk factor for morbidity and mortality globally, responsible for an estimated 3.9 million premature deaths per year and approximately 4.8 % of disability-adjusted life years [3,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation